Strategies for Chemical Control of Root-knot Nematodes (Meloidogyne spp.) in Established Vineyards - Loubsera, J.T.; Meyer, A.J. (South African Journal of Enology and Viticulture, 2017)
Grape-vine root growth was measured for vertical and horizontal distribution as well as seasonal growth periods. The persistance of aldicarb and fenamiphos in the soil as well as in leaves and fruit of grape-vines was monitored over a prolonged period to establish behaviour patterns which inflnence chemical control strategies. Most roots occurred within 600 mm from the trunk, both vertically and horizontally. Two periods of root development occurred annually. Accordingly applications of nematicides should be made in a band covering 600 mm on both sides of the vine trunk, either after harvest and/or during budburst. Results on residues of aldicarb and fenamiphos stress the importance of adequate water supply after application. Both nematicides will reach the bulk of the roots if correctly placed and were still detected after 42 days and 70 days respectively. Applications during spring with aldicarb and fenamiphos at the dosages used will have no effect on the fermentation of grape musts nor result in toxic residues exceeding 0,05 mg/kg in the grapes.